An Interdisciplinary Approach: Presentation of the Pediatric Obstructive Sleep Apnea Diagnostic Examination Form (POSADEF) - Janine Sambale; Richard Birk; Ulrich Koehler; Wulf Hildebrandt; Heike Maria Korbmacher-Steiner (Diagnostics, 2024)
This report emphasizes the need for interdisciplinary collaboration in diagnosing and treating pediatric obstructive sleep apnea (OSA). OSA, affecting 1% to 4% of children, often results from adenotonsillar hypertrophy, craniofacial disorders, or obesity. While adenotonsillectomy is the primary treatment, about 75% of children, especially those with craniofacial disorders or obesity, continue to experience OSA symptoms post-surgery. To address these cases, several medical fields emphasize the necessity and demand for interdisciplinary collaboration in managing pediatric OSA. Therefore, the authors aimed to develop the Pediatric Obstructive Sleep Apnea Diagnostic Examination Form (POSADEF). This form, based on clinical experience and the literature, captures craniofacial and functional characteristics linked to pediatric OSA. A case study of an eight-year-old girl with OSA, who was unsuccessfully treated with adenotonsillectomy, underlines the importance of the diagnostic examination form. The orthodontic assessment revealed craniofacial disorders and subsequent treatment with maxillary expansion and functional appliance therapy resolved her OSA symptoms. This case demonstrates the value of POSADEF in enabling comprehensive evaluation and treatment across medical disciplines. POSADEF is designed to assist health care professionals in diagnosing craniofacial and orofacial anomalies contributing to pediatric OSA.